Politics and the corporation - Prechel, Harland (Research in political sociology, 2005)
Focuses on the ways in which corporations exercise political power, and how changes in the political-legal arrangements in which corporations are embedded affect their organizational behavior. This volume examines the historical and dialectical relationship between the corporation and the state.